1979
DOI: 10.1038/bjc.1979.278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human, bovine and ovine prolactin on DNA synthesis by organ cultures of benign human breast tumours

Abstract: Summary.-Ten benign breast tumours from 9 female patients (8 with fibrocystic disease and 1 with fibroadenoma) and I male patient (with gynaecomastia) were processed into slices and individually cultured for 2 days in serum-free Medium 199.[3H]-TdR was added to the culture medium to assess DNA synthesis. The addition of human prolactin to the culture medium (500 ng/ml) significantly (0-05 > P > 0.01) increased DNA synthesis; all 9 biopsy specimens from the 9 female patients responded positively to this hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…However, at higherconcentrations, above physiological, this preparation ofhGH was more effective than was the oPRL preparation. This observation is similar to reports of others (23,24). Clearly, however, both hGH and oPRL are lactogenic and have similar biological potency within the physiological range.…”
supporting
confidence: 92%
“…However, at higherconcentrations, above physiological, this preparation ofhGH was more effective than was the oPRL preparation. This observation is similar to reports of others (23,24). Clearly, however, both hGH and oPRL are lactogenic and have similar biological potency within the physiological range.…”
supporting
confidence: 92%
“…Several authors [25,26] have reported that both ovine and bovine prolactin stimulated DNA synthesis in the epithelium of such tissues. We had earlier found an increase in the 3H-thymidine incorporation into DNA in benign lesions in the presence of these hormones [16], but this increase was not significant. On the other hand, human prolactin had a significant effect on 2-day cultures of benign breast lesions.…”
Section: Discussionmentioning
confidence: 72%
“…We had previously studied the two most commonly analyzed experimental models for human breast cancer, i.e., the spontaneous mouse mammary carcinoma and the DMBA-induced rat mammary carcinoma [1,7], as well as benign [2,6,16,17] and malignant [1,4] lesions of human breast epithelium, and had found that insulin and hydrocortisone have the capacity to consistently stimulate DNA synthesis in tissue culture. Others (18) have reported a similar response with benign human breast tumors grown in athymic nude mice, suggesting the importance of such hormones in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…The prolactin receptor is expressed in almost all cell types and in 70% of breast cancer samples (Vonderhaar 1989). Early studies demonstrated that physiological concentrations of prolactin could induce proliferation of primary human breast tumors in organ culture and tumor-derived primary cells in culture (Welsch et al 1979;Malarkey et al 1983). In addition, prolactin induces proliferation of breast cancer-derived cell lines such as MCF-7 and T47D under serum-free conditions or in the presence of charcoal-stripped serum (Biswas and Vonderhaar 1987;Vonderhaar 1999).…”
Section: Prolactin and Breast Cancermentioning
confidence: 99%